The Role of Chicken Prolactin, Growth Hormone and Their Receptors in the Immune System - Mo, Guodong; Hu, Bowen; Wei, Ping; Luo, Qingbin; Zhang, Xiquan (Frontiers in Microbiology, 2022)
Hormones like prolactin (PRL) and growth hormone (GH) exhibit important roles in the immune system maintenance. PRL and GH are polypeptide hormones secreted by pituitary, with a wide range of physiological functions, including biosynthesis, metabolism, and immune response. In poultry, PRL mainly plays its roles in nesting, hatching, and reproduction, while GH is primarily responding to body weight, fat formation and feed conversion. Meanwhile, PRL and GH act as cytokines involved in the immune response of poultry. In this review, we attempt to provide a critical overview of the relationship between PRL and GH, PRLR and GHR, and the immune response of poultry. We also propose a hypothesis that PRL, GH and their receptors might be used by viruses as viral receptors. This may provide new insights into the pathogenesis of viral infection and host immune response, along with new potential therapeutic strategies.